Universal Fuzzy Controllers for Non-affine Nonlinear Systems - Gao, Qing.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This thesis provides a systematic and integral answer to an open problem concerning the universality of dynamic fuzzy controllers. It presents a number of novel ideas and approaches to various issues including universal function approximation, universal fuzzy models, universal fuzzy stabilization controllers, and universal fuzzy integral sliding mode controllers. The proposed control design criteria can be conveniently verified using the MATLAB toolbox. Moreover, the thesis provides a new, easy-to-use form of fuzzy variable structure control. Emphasis is given to the point that, in the context of deterministic/stochastic systems in general, the authors are in fact discussing non-affine nonlinear systems using a class of generalized T-S fuzzy models, which offer considerable potential in a wide range of applications.
Introduction -- Universal Fuzzy Models and Universal Fuzzy Controllers for Non-affine Nonlinear Systems -- Universal Fuzzy Models and Universal Fuzzy Controllers for Stochastic Non-affine Nonlinear Systems -- Sliding Mode Control Based on T-S Fuzzy Models -- Universal Integral Sliding-Mode Fuzzy Controllers for Non-affine Nonlinear Systems -- Universal Integral Sliding-Mode Fuzzy Controllers for Stochastic Non-affine Nonlinear Systems -- Concluding Remarks.
Keywords: Control engineering; Computational intelligence; System theory; Control theory; Mathematical models; Control and Systems Theory; Computational Intelligence; Systems Theory, Control; Mathematical Modeling and Industrial Mathematics